Image Skills in Iqbal Mirza’s Poetry - Muyassar Mustafoyeva, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article analyzes the lyrical experience and artistic imagery in Iqbal Mirza’s poetry on the basis of poetic examples.